2017
DOI: 10.5539/ijel.v8n1p119
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Presentation as an Index of Style: A Comparative Corpus Stylistic Analysis of Self and Other Translators

Abstract: This study aims to explore the style of other and self-translators in comparison with non-translated texts, assuming discourse presentation as an indicator of style. Theoretically, other and self-translators are considered different in their translation style. The reason is that self-translators enjoy more liberty and authority over the source text as compared to other-translators (Bozkurt, 2014; Cordingley, 2013). However, practically, previous studies have explored either the style of self-translators (Ehrli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The results revealed that the three translators make distinguished repeated choices of person and tense for the same type of DP. In addition, different groups of translators' preferences for a specific mode of DP can also differentiate one translator from the other (Obaid et al, 2017). The results of Obaid et al's (2017) study manifested that self-translators were more subjective and characteroriented than the other translators, who were more intent to choose FDS corresponding to the same type of DP in the ST. Angermeyer (2009) also argued that different court interpreters' choice of DS and IS in the court interpreting show their closeness to the norms of the court or the target audience.…”
Section: Speech Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the three translators make distinguished repeated choices of person and tense for the same type of DP. In addition, different groups of translators' preferences for a specific mode of DP can also differentiate one translator from the other (Obaid et al, 2017). The results of Obaid et al's (2017) study manifested that self-translators were more subjective and characteroriented than the other translators, who were more intent to choose FDS corresponding to the same type of DP in the ST. Angermeyer (2009) also argued that different court interpreters' choice of DS and IS in the court interpreting show their closeness to the norms of the court or the target audience.…”
Section: Speech Presentationmentioning
confidence: 99%
“…The findings on the development of Barr's translation style and its motivations can offer a new interpretation of Chinese-English translations and the nature of translation. Among over 40 stylistic indicators that have been applied in the translator's style studies, the speech and thought presentation (Huang, 2015;Obaid, Mahmood, Iqbal, & Zahoor, 2017;Winters, 2007Winters, , 2010 is the most frequently observed pragmatic stylistic indicator (Li et al, 2022). Previous studies proved that discourse presentation was a sensitive stylistic indicator that distinguished one translator's style from the other.…”
Section: Introductionmentioning
confidence: 99%
“…Various theories for classifying and identifying them, such as Newmark's typology for the translation of metaphor [24] and Biber's function categorization of lexical bundles [18], has been used. In addition, to analyze the translator's repeated choices in the translation from the pragmatic aspect, Halliday's theory of systematic functional linguistics [25], Semino and Short's framework of discourse presentation [26], and the theories of narrative stylistics can be utilized. Nevertheless, very few theories have been developed or put into practice by scholars for the phase of examining the shaping mechanism of the translator's style.…”
Section: Research Theories Of the Translator's Style Studymentioning
confidence: 99%
“…Originalmente, este modelo ha sido utilizado para observar el estilo en la literatura narrativa de ficción. Sin embargo, nuevas aplicaciones de este se han realizado con el objetivo de examinar otros tipos de corpus con diversos propósitos, entre los que se encuentran el análisis de la presentación del habla y del pensamiento en el discurso de predicadores islámicos (Zahara & Syarif, 2019) y en el discurso bíblico (Al-Ameedi & Al Shamiri, 2018), el análisis de la presentación del discurso en cómics (Tang, 2016), el análisis de presentación del discurso como indicador de estilo en traducciones (Obaid et al, 2017) y el análisis de presentación del habla y el pensamiento para medir la comprensión y apreciación de la prosa de ficción en estudiantes (Tuncer, 2017). Por lo anterior, se reconoció esta tendencia de aplicación en otros tipos de corpus para observar cómo se manifiesta en un corpus elicitado a través del recuento de una historia de ficción por parte de jóvenes escolarizados.…”
Section: S Presentation Of Speech [Nsps] Narrator's Presentation Of T...unclassified